Methylome Analysis and Epigenetic Changes Associated with Menarcheal Age - Demetriou,CA; Chen,J; Polidoro,S; van,Veldhoven K; Cuenin,C; Campanella,G; Brennan,K; Clavel-Chapelon,F; Dossus,L; Kvaskoff,M; Drogan,D; Boeing,H; et al. (PLOS One, 2013)
Reproductive factors have been linked to both breast cancer and DNA methylation, suggesting methylation as an importantmechanism by which reproductive factors impact on disease risk. However, few studies have investigated the link betweenreproductive factors and DNA methylation in humans. Genome-wide methylation in peripheral blood lymphocytes of 376healthy women from the prospective EPIC study was investigated using LUminometric Methylation Assay (LUMA). Also,methylation of 458877 CpG sites was additionally investigated in an independent group of 332 participants of the EPIC-Italysub-cohort, using the Infinium HumanMethylation 450 BeadChip. Multivariate logistic regression and linear models wereused to investigate the association between reproductive risk factors and genome wide and CpG-specific DNA methylation,respectively. Menarcheal age was inversely associated with global DNA methylation as measured with LUMA. For eachyearly increase in age at menarche, the risk of having genome wide methylation below median level was increased by 32%(OR:1.32, 95%CI:1.14–1.53). When age at menarche was treated as a categorical variable, there was an inverse dose-responserelationship with LUMA methylation levels (OR12–14vs.#11 yrs:1.78, 95%CI:1.01–3.17 and OR$15vs.#11 yrs:4.59, 95%CI:2.04–10.33; P for trend,0.0001). However, average levels of global methylation as measured by the Illumina technology were notsignificantly associated with menarcheal age. In locus by locus comparative analyses, only one CpG site had significantlydifferent methylation depending on the menarcheal age category examined, but this finding was not replicated bypyrosequencing in an independent data set. This study suggests a link between age at menarche and genome wide DNAmethylation, and the difference in results between the two arrays suggests that repetitive element methylation has a role inthe association. Epigenetic changes may be modulated by menarcheal age, or the associatio